Experimental study on the disintegration behavior and mechanism of red-bed mudstone in guangxi, China - Luo, Tingyi; Zhang, Qingsong; Gui, Chong; Tang, Yasen; Zhou, Shijie; Wang, Yuting (Frontiers in Materials, 2024)
Red-bed mudstone (RBM) has the characteristics of being easily softened and disintegrated under dry and wet cycles. To investigate the weakening and disintegration characteristics of the RBM, typical mudstone from Guangxi highway slope was taken as the research object in this study. Disintegration tests, water chemistry tests, and microscopic tests were performed to investigate the disintegration mechanism of this RBM. The results indicate that the RBM exhibits strong disintegration, releasing soluble salts such as potassium chloride and sulfates during the disintegration process. The hydrolysis of clay minerals is the main cause of changes in ion concentration in the solution. Throughout the dry and wet cycles, the proportion of macro-pores and meso-pores significantly increases, while the percentage of small and micropores gradually decreases. Under the influence of dry and wet cycles, the contact area between particles gradually decreases, transitioning from face-to-face contact to face-edge contact and finally to edge-to-edge contact. These research findings provide a basis for the stability analysis and prevention of landslide hazards in the red-bed soft rock areas.